Effect of Nutrition Education on the Dietary Habits of Secondary School Students in Delta State, Nigeria - APAOKUEZE, Tessy N. (Ilorin Journal of Education, 2025)
This quasi-experimental study examined the impact of nutrition education on dietary habits and nutrition knowledge among secondary school students in Delta State, Nigeria. Six hundred five students from 12 mixed public secondary schools in Delta Central Senatorial District participated, with students randomly assigned to an experimental group receiving nutrition education and a control group following conventional instruction. Data were collected using validated instruments: a Nutrition Knowledge Test (NKT) and a Dietary Habit Questionnaire (DHQ), administered before and after a three-month intervention consisting of weekly nutrition education sessions. Statistical analyses, including t-tests and logistic regression, assessed nutrition knowledge and changes in dietary habits. Results demonstrated significant improvements in the experimental group's nutrition knowledge across most domains, particularly in nutritional recommendations, nutrient sources, and diet–disease relationships (p < 0.001), except in daily food choices where no significant difference was observed. Dietary habits also improved markedly, with the experimental group scoring significantly higher (mean = 47.83) than controls (mean = 23.64). Gender analysis revealed that females benefited more from the intervention, showing significantly higher dietary habit scores than males (p < 0.05). Findings indicate that nutrition education substantially enhances nutrition knowledge and dietary habits among secondary school students, with gender-specific responses suggesting the need for tailored educational approaches. This study underscores the importance of integrating nutrition education into school curricula to promote healthier dietary behaviours and improve student well-being.